Bibliometric Analysis of Research Trends in STEM Education and Higher-Order Thinking Skills (HOTS) in Physics Learning - Niken Uswatun Alimah; I Made Astra; Iwan Sugihartono; Firmanul Catur Wibowo (Jurnal Ilmiah Pendidikan Fisika, 2025)
This study presents a bibliometric analysis of research trends in STEM (Science, Technology, Engineering, and Mathematics) education and Higher-Order Thinking Skills (HOTS) within the context of physics learning. The aim is to identify dominant research themes, visualize their development over time, and uncover gaps in the integration of STEM and HOTS in physics education. A total of 147 articles published between 2017 and 2024 were retrieved from the Scopus database, with 96 articles selected for analysis. VOSviewer was used to generate three types of visualizations: network visualization to explore keyword relationships, overlay visualization to track thematic trends over time, and density visualization to examine research concentration. The results reveal that: (1) research on STEM, HOTS, and physics learning has grown significantly, especially since 2021; (2) overlay visualization indicates a shifting research focus toward integrating HOTS through STEM approaches in physics contexts; (3) density mapping shows that the integration of HOTS in STEM-based physics instruction remains relatively underexplored; (4) content analysis highlights that STEM is commonly connected with the development of essential thinking skills, the integration of student-centered learning models such as Project-Based Learning and Problem-Based Learning, and the use of digital learning media; and (5) recent studies have also begun to emphasize the importance of considering affective domains, such as students’ scientific attitudes, motivation, and engagement, in the implementation of STEM-based learning. This study provides a structured overview of the STEM-HOTS research landscape, offering both theoretical insights and practical implications for advancing innovative, skill-oriented physics instruction.